PENERAPAN PRINSIP-PRINSIP KOMUNIKASI ISLAM TERHADAP KETENANGAN JIWA ORANG TUA LANJUT USIA PADA PANTI JOMPO RUMOH SEUJAHTRA GEUNASEH SAYANG BANDA ACEH - Tisi Maulidya Putri (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2017)
Abstrak: This study aims to determine the implementation of Islamic communication principlestoward the peace of soul of the elderly, the response and the obstacle in implementing Islamic communicationprinciples at Nursing Home Rumoh Seujahtra Geunaseh Sayang of Banda Aceh. In thisstudy, the writer used the theory of S-O-R which is an abbreviation of Stimulus - Organism - Response.In addition, she used a qualitative approach with direct observation at Nursing Home RumohSeujahtra Geunaseh Sayang of Banda Aceh and conducted interviews with health workers, psychologists,religious teachers, caregivers and the elderly.